Long-term effects of elevated CO2 on the population dynamics of the seagrass Cymodocea nodosa: Evidence from volcanic seeps. (January 2021) - Mishra, A.K.; Cabaço, S.; de los Santos, C.B.; Apostolaki, E.T.; Vizzini, S.; Santos, R.
Abstract: Population reconstruction techniques was used to assess for the first time the population dynamics of a seagrass, Cymodocea nodosa, exposed to long-term elevated CO2 near three volcanic seeps and compared them with reference sites away from the seeps. Under high CO2, the density of shoots and of individuals (apical shoots), and the vertical and horizontal elongation and production rates, were higher than at the reference sites. Nitrogen limitation effects on rhizome elongation and production rates and on biomass were more evident than CO2 as these were highest at the location where the limitation of nitrogen was highest. At the seep where the availability of CO2 was highest and nitrogen lowest, density of shoots and individuals were highest, probably due to CO2 effects on shoot differentiation and induced reproductive output, respectively. At the three seeps, there was higher short- and long-term shoot recruitment than at the reference sites, and growth rates was around zero, indicating that elevated CO2 increases the turnover of C. nodosa shoots. Highlights: Long-term CO2 enrichment increases C. nodosa shoot density and rhizome elongation and production rates. No changes in the population biomass were observed under high CO2 . Nitrogen limitation effects on rhizome elongation, production rates and on biomass were stronger than CO2 . Elevated CO2 increases C. nodosa shoot recruitment and turnover rates. Replication of CO2 seeps is necessary to capture responses to long-term CO2 enrichment.